A commentary on the International Covenant on Civil and Political Rights : The UN Human Rights Committee's Monitoring of ICCPR Rights / Paul M. Taylor. - Taylor, Paul M., 1958- (Cambridge University Press, 2020)
A new and an essential reference work for any international human rights law academic, student or practitioner, A Commentary on the International Covenant on Civil and Political Rights spans all substantive rights of the International Covenant on Civil and Political Rights (ICCPR), approached from the perspective of the ICCPR as an integrated, coherent scheme of rights protection. In detailed coverage of the Human Rights Committee's output when monitoring ICCPR compliance, Paul M. Taylor offers extraordinary access to forty years of its Concluding Observations, Views and General Comments organised thematically. This Commentary is a solid and practical introduction to any and all of the civil and political rights in the ICCPR, and a rare resource explaining the requirements for domestic implementation of ICCPR standards. An indispensable research tool for any serious enquirer into the subject, the Commentary speaks to the accomplishments of the ICCPR in striving for universal human rights standards.